2007
DOI: 10.1155/2007/15481
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Peroxisomal Enzyme Activities and Cytochrome P450 4A Isozyme Expression by Congeneric Polybrominated and Polychlorinated Biphenyls

Abstract: The purpose of this study was to determine the effects of PCBs and PBBs on peroxisome proliferator-activated receptor-α-(PPARα-) associated enzyme activities or protein levels. Male Sprague-Dawley rats were administered a single IP injection (150 μ mol/kg) of either 3,3′,4,4′-tetrabromobiphenyl, 3,3′,4,4′-tetrachlorobiphenyl, 3,3′,5,5′-tetrabromobiphenyl, 2′,3,3′,4,5-pentachlorobiphenyl, 3,3′,4,4′,5-pentachlorobiphenyl, 2,2′,3,3′,5,5′-hexachlorobiphenyl, or 3,3′,4,4′,5,5′-hexabromobiphenyl in corn oil (10 ml/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Recent studies have demonstrated PCBs’ interaction with other nuclear receptors including human PXR and rodent peroxisome-proliferator activated receptor alpha (PPARα) (Al-Salman and Plant, 2012; Robertson et al, 2007; Wahlang et al, 2014). We hypothesized that Aroclor 1260 may interact with these receptors in our animal model.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated PCBs’ interaction with other nuclear receptors including human PXR and rodent peroxisome-proliferator activated receptor alpha (PPARα) (Al-Salman and Plant, 2012; Robertson et al, 2007; Wahlang et al, 2014). We hypothesized that Aroclor 1260 may interact with these receptors in our animal model.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction in hepatic SeGPx activity may increase oxidative stress by reducing the liver’s capacity to remove hydrogen peroxide. In a separate study we found that PCB 126 also suppresses hepatic catalase activity, further diminishing the liver’s ability to remove hydrogen peroxide (Robertson et al 2007). The PCB 126-induced decrease in total GPx activity, which consists of both SeGPx and glutathione transferase (GST) activities, was diminished, but at a lower magnitude to that of SeGPx, suggesting an induction of GST (Prohaska 1980; Schramm et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…For peroxisome proliferator activated receptors (PPARs) Ariyoshi et al (1998) and Robertson et al (2007) found that the highly toxic more co-planar PCB 126 acts as inverse agonist and reduces liver peroxisomal enzyme activity in the rat model. Other co-planar meta-and parasubstituted PCBs should have the same potential (Ludewig et al, 2007).…”
Section: Other Activated Receptorsmentioning
confidence: 99%